INVESTIGATING QUASI-PERIODIC OSCILLATION SIGNATURES IN THE DYONIC MODMAX MODEL USING QUASAR DATA (Scientific journal of the Fergana State University, 2026)
In this study, we explore quasi-periodic oscillations produced near a black hole governed by the Dyonic ModMax metric. By fitting the QPO frequencies recorded from the micro-quasars GRO J1655-40, XTE J1550-564, XTE J1859+226, GRS 1915+105 and H1743-322, we establish observational limits on the charge Q and coupling γ parameters of the model. The constraints are derived through a Monte Carlo Markov Chain analysis of the data, yielding refined estimates that sharpen our understanding of black-hole behaviour within the Dyonic ModMax framework.